On-farm performance of wheat grown on sodic soils irrigated with high RSC water in arid regions of Rajasthan - KUMAR, MAHESH; SINGH, RAJ; KUMAWA, R. N. (Journal of Soil and Water Conservation, 2020)
With the commencement of tube-well technology, farmers of the western Rajasthan started use of ground water for irrigating arable crops. The ground water of this tract has problems of high residual sodium carbonate (RSC) and salinity. Continuous use of such poor quality irrigation water caused accumulation of salts on the soil surface due to edaphic and climatic reasons and made soils unfit for cultivation. Farmers’ participatory research intervention trials on sodic soil reclamation in farmer’s participatory mode were conducted at 12 sites of Barmer and Jodhpur districts of Rajasthan to demonstrate the effect of gypsum application on yield and yield attributes of wheat. Four levels of gypsum [100, 50, 25 and 0 % (without gypsum) of soil gypsum requirement] were used in the trials. Results of the trials showed that gypsum application decreased soil pH by 0.3 to 1.1 units. The availability of P, Fe and Zn in rhizosphere increased by 25.91, 32.72 and 38.46% over control with the application of gypsum @100 % of GR. Application of gypsum at 50 % of GR while remaining at par with 100 % of GR increased plant height, tillers/plant, leaves/plant and ear length by 13.16, 22.98, 23.12 and 13.82 % over control. The grain and straw yields increased to the tune of 39.72 and 37.58 % with 50 % GR compared to control that recorded 2.87 and 3.65 t/ha yield, respectively.